2013
DOI: 10.1016/j.radphyschem.2012.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of epoxy coatings under gamma irradiation

Abstract: c The effects of irradiation at three distinct dose rates have been studied on two epoxy networks. c DGEBA-polyamidoamine networks appear more stable than DGEBA-polyoxypropylene diamine ones. c A simple kinetic model involving methyl ketones is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…In our previous study of radiation induced oxidation [2], we have put in evidence the formation of a methyl ketone (MK) absorbing at 1722 cm −1 .…”
Section: These Changes Call For the Following Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study of radiation induced oxidation [2], we have put in evidence the formation of a methyl ketone (MK) absorbing at 1722 cm −1 .…”
Section: These Changes Call For the Following Commentsmentioning
confidence: 99%
“…In a recent publication [2], we have reported results of an investigation aimed to explore essentially the regime (I) for both systems under study. Some peculiarities of POPA and PAA structures were put in evidence and it was shown that, for the dose rates of practical interest (≤0.1 Gy h −1 ), aging is dominated by thermal oxidation (regime III), that justifies this work.…”
Section: Introductionmentioning
confidence: 99%
“…Without oxygen, the "weak point" carbons may be reacted with alkyl radical in the chemical reaction (3) as illuminated in Ref. [28], where unsaturated carbon bond (C]C) generates as confirmed by FT-IR analysis. These reactions result in polymer chain scission and degradation of the resin matrix.…”
Section: Xps Analysismentioning
confidence: 87%
“…When the resin matrix is exposed to g irradiation, alkyl radicals are formed in the whole volume of the resin matrix, as shown in the chemical reaction (1). It is reported that the isopropanol segment of the epoxy network is the "weak point", where the three carbons (a, b and c) are relatively susceptible to radical attack [28]. The reactions between alkyl radicals and "weak point" are different with and without O 2 .…”
Section: Xps Analysismentioning
confidence: 99%
“…The composite matrix and materials are simulated on the ground to understand the behavior of the composite matrix and materials on the radiation effects . Several studies on the radiation effects on matrix properties have been carried out by researchers, which include epoxy, low‐density polyethylene, and high‐density polyethylene (HDPE); blends of resins as cyanate ester/epoxy, cyanate ester/benzoxazine . In addition to these the radiation effects on the composite's properties, such as epoxy/glass fiber, epoxy/B 4 C, epoxy/halloysite nanotubes, epoxy/aluminium, HDPE/B 4 C, and HDPE/hydroxyapatite nanocomposite, are also studied.…”
Section: Introductionmentioning
confidence: 99%